Microtubules and mechanosensing: key players in endothelial responses to mechanical stimuli - Danahe Mohammed; Ibrahim Hamid; Benoit Vanhollebeke; Maud Martin (Cellular and Molecular Life Sciences)
Abstract The vascular mechanical microenvironment is characterized by dynamic forces such as blood flow, stretch, and matrix stiffness, which profoundly influence endothelial cell (EC) behavior. ECs detect these forces through specialized mechanosensing structures and activate mechanotransduction pathways to adapt their responses and maintain vascular homeostasis. While actin filaments and focal adhesions are well-established mediators of these processes, emerging evidence highlights microtubules as critical players in endothelial mechanotransduction. Composed of α- and β-tubulin, microtubules are stiff elements forming a dynamic and adjustable network that regulates cell polarity, migration, and signaling. Their characteristics make them interesting candidates as essential regulators in force sensing, modulating cellular stiffness and adaptation to mechanical constraints. In this Review, we discuss the role of microtubules in endothelial mechanosensing, emphasizing their contribution to force perception and cellular adaptation. Specifically, we describe their involvement in shear stress sensing, curvature and matrix stiffness detection, pressure response, and topographical sensing. Furthermore, we highlight how microtubules are dynamically modified upon mechanical cues and explore the role of post-translational modifications, particularly acetylation, in regulating their mechanical properties. These insights provide a new perspective on endothelial responses to mechanical stimuli, offering potential therapeutic avenues in the context of pathological angiogenesis, where microtubule regulation may play a crucial role.